Internal banking supervision requirements and their impact on the development of electronic accounting information systems: Applied research in a sample of Iraqi private banks (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Despite the availability of information technology banking features and benefits of the banking sector, they involve many risks and challenges and put in the face of the administrative authorities and regulatory institutions in the banking system, organizational matters and control sensitive and bear direct responsibility for conducting independent assessments of their regulatory and information and determine the degree of its durability and its ability to confront problems imposed by the technical challenges and technological . And the success of the administrative authorities and regulatory institutions in achieving its objectives in the management of risks and threats oversight resulting from the activities and operations of electronic banking entails the development and adaptation of control procedures and tools to the provisions of the control of the threats and the additional risks posed by the use of accounting information systems electronic banking industry because of the characteristics and the nature of their activities , and requires the availability of a set of basic properties of systems in information and communication technology that make up the infrastructureoftheactivityandinternalcontrolsystems. This study is a form of surveys aimed in which Applied to discover the current status of the internal control systems in private banks in Iraq and assess the degree of robustness and effectiveness of the procedures and controls designed in information systems, accounting and electronic determine the compatibility of the characteristics of the regulatory system for accounting information systems Computerized used with regulatory requirements and procedures of public accepted, from the standpoint of working in Iraqi banks and external auditors in these banks .